The age of innocence eaudiobook - Wharton, Edith (Recorded Books Inc., 2013)
Newland Archer is a young lawyer, a member of New York's high society, and engaged to be married to May Welland. Countess Ellen Olenska is May's cousin, and wants a divorce from the Polish nobleman she married. Intelligent and beautiful, she comes back to New York where she tries to fit into the high society life she had before her marriage. Her family and former friends, however, are shocked by the idea of divorce within their social circle, and she finds herself snubbed by her own class. Ellen and Newland fall in love and must choose between passion and conventions.